Minangkabau’s Marriage and Delik Adat Laws in Abdulkarim Khiratullah’s Mencari Cinta Yang Hilang - ., Purwarno; Suhendi, A (KnE Social Sciences, 2018)
This research aims at analysing two of the Minangkabau’s Adat Laws: marriage and delik adat laws reflected in Abdulkarim Khiratullah’s Novel Mencari Cinta Yang Hilang (2008). The theory of the Minangkabau’s Adat Law used as the basis of analysing the data in this research is proposed by Soekanto (2010). The method used in this research is qualitative descriptive method proposed by Moleong (2004). The research result shows that the existence of Minangkabau’s marriage and delik adat laws have caused the protagonist of the novel named Fauzi encountered some certain obstacles to marry a girl whom he loves so much, named Rahima. Even though he has tried his best to materialize his love to Rahima, the marriage as well as delik Adat Law prevailing in his society has made him fail to marry Rahima. He fails in marrying his beloved girl as the girl is of the same clan as his, and it is strickly forbiden for a man in Minangkabau’s adat law to marry a woman from the same clan as he. Keywords: adat, inheritance, marriage adat law, delik adat law, kinship